ANALISIS STABILITAS LERENG TAMBANG BATUBARA TERBUKA DI BANKO TENGAH SUBAN JERIJI - Ori Patinsyah; Muhammad Yusa; Gunawan Wibisono (Jurusan Teknik Sipil Universitas Bangka Belitung, 2021)
Coal is one of the most important fuels for the sustainability of steam powered engines, be it power plants or industrial machines. In addition, safe mining activities are very important in the mining process, due to its importance it is necessary to analyze slope stability with the aim of obtaining safe slopes for miners so that mining activities can run smoothly. The analysis method used is with the help of the Geoslope 2018 program where the stability analysis will be carried out on 3 slopes, namely, single slopes, inter-ramp slopes and overall slopes. The results of the stability analysis carried out on a single slope were obtained, the safety number for the D overburden layer was 1.606, for the D seam layer the safety figure obtained was 2.045, for the DE interburden layer the security number was 1.397, on the E seam layer the analysis results obtained a safety number of 1.333 , and for the underburden E layer, the results of the single slope analysis that have been carried out obtained the safety number 1.396. For the analysis of inter-ramp slope stability, the safety rate on ramp 1 is 2.194, on ramp 2 is 1.260 and on ramp 3 is 1.191. Thus, from the stability analysis of single slopes and inter-ramp slopes can be designed and analyzed the overall slope stability and obtained a safety figure of 1.124 with the slope of the slope is 15o at a depth of 200 m.